Nano-Structured Lipid Carriers (NLCs) as a Novel Nanotechnological Strategy for Improving the Oral Drug Bioavailability - Thamer, Saad M.; Allami , Mohammed S. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Nanotechnology has transformed pharmaceutical science by enabling nanoscale delivery systems that overcome major limitations in conventional oral drug administration, including poor solubility, instability, and extensive first-pass metabolism. Specific Background Among lipid-based nanocarriers, nanostructured lipid carriers (NLCs) have emerged as a second-generation advancement over solid lipid nanoparticles due to their mixed solid–liquid lipid matrix. Knowledge Gap Despite extensive research, the mechanisms by which NLCs enhance oral bioavailability and their comparative advantages across formulation techniques remain insufficiently synthesized. Aims This work consolidates current evidence on the structure, preparation, stability, and functional performance of NLCs as oral drug delivery systems. Results The review indicates that the imperfect or amorphous NLC matrix increases drug loading, modulates release kinetics, improves physicochemical stability, reduces required surfactant concentrations, and promotes lymphatic uptake while attenuating P-glycoprotein efflux. Novelty By integrating mechanistic, formulation, and biopharmaceutical insights, this synthesis highlights the multidimensional superiority of NLCs in enhancing the oral absorption of poorly soluble and labile drugs. Implications NLCs represent a promising platform for next-generation oral therapeutics, with potential to improve clinical efficacy, reduce dosing frequency, and expand the applicability of challenging drug molecules despite remaining manufacturing and regulatory hurdles.Highlight : NLCs provide higher drug loading and reduce crystallization-related leakage. Their small particle size and lipid composition enhance oral absorption and lymphatic uptake. Scalable manufacturing methods support consistent, controlled drug release. Keywords : Nanotechnology, Oral Drug Delivery, Lipid-Based Nanocarriers, Nanostructured Lipid Carriers, Bioavailability